Metabolomics Reveals the Mechanisms for the Pulmonary Toxicity of Siegesbeckia orientalis L. and the Toxicity-Reducing Effect of Processing - Jiang, Ting; Liu, Linsheng; Zhang, Mi; Qiao, Zhiping; Zhao, Tingxiu; Su, Junfang; Cao, Gang; Su, Tao (Frontiers in Pharmacology, 2021)
Siegesbeckia orientalis L. (SO) is a commonly used Chinese medicinal herb. It has long been used as a remedy in traditional Chinese medicine (TCM) for symptoms that resemble inflammatory joint disorders. However, it is slightly toxic. According to the TCM theory, processing can reduce the toxicity of the herbs. Here, we performed metabolomics to determine whether processing with rice wine reduces the toxicity of raw SO, and to explore the mechanisms underlying the raw SO-induced toxicity and the toxicity-reducing effect of processing. Our results showed that raw SO has long-term toxicity in rats. It significantly elevated the serum level of LDH, and caused histopathological damages in the lung tissues. It is worth noting that, the LDH level in PSO group was lower than that in raw SO group, and the damages in lung tissues were relatively mild in PSO-treated rats, suggesting that processing reduces the pulmonary toxicity of the raw. Moreover, a total of 32 significantly changed metabolites were identified. Based on the metaboanalyst pathway analysis, we found that two characteristic metabolic pathways including arginine biosynthesis and glycerophospholipid metabolism were only changed in raw SO group; while, histidine metabolism was only changed in raw PSO group, which suggests that induction of oxidative stress contributes to raw SO-induced pulmonary toxicity, and free radical scavenging might be responsible for the toxicity-reducing effect of processing. Our data shed new light on how raw SO induces pulmonary toxicity and how the toxicity can be reduced by processing. This study not only provides scientific justifications for the traditional processing theory of SO, but also helps to optimize the processing protocol and the clinical drug combination of SO.